The Relationship between Strategic Leadership, Competitive Advantage and Intellectual Capital : Evidence from Hotel in Tangerang Indonesia - Rr Dian Anggraeni; Tubagus Ismail; Tri Lestari; Dadan Ramdhani (Britain International for Academic Research (BIAR) Publisher, 2023)
This study is accomplished to reveal the relationship between strategic leadership, competitive advantage, intellectual capital by examining from the effect of strategic leadership on competitive advantage with intellectual capital as intervening variable. The sample used in this study is a company in the hotel sector in the city of Tangerang, Indonesia. Competitive advantage is one of the most important variables that can determine the capabilities of the companies. Other variable like strategic leadership also contributes on creating competitive advantage. On the other hand, the application of strategic leadership cannot be separated from the support of intellectual capital in the companies. The data analysis technique used in this study was partial least square to describe the relationship among variables. The result of this study showed that strategic leadership and intellectual capital affected competitive advantage positively and significantly in company in the hotel sector in the city of Tangerang, Indonesia.